Dual Trigger with Gonadotropin Releasing Hormone Agonist and Human Chorionic Gonadotropin of Fresh Autologous Cycles in High Responders: A Systematic Review - AA Vyrides; EE Mahdi; D Lamnisos; K Giannakou (JRI, 2022)
Background: The purpose of the current study was to investigate the effect of coadministration of human chorionic gonadotropin (hCG) with gonadotropin releasing hormone agonist (GnRH-a) trigger (dual trigger) in high responders for fresh autologous cycles in order to investigate the pregnancy outcomes and rates of ovarian hyperstimulation syndrome (OHSS) in comparison to GnRH-a trigger alone. Methods: A systematic search was performed in PubMed and Ovid MEDLINE from inception through February 2020. The included materials were case-control, cohort and, cross-sectional studies as well as clinical trials in which the outcomes of dual trigger with GnRH-a were compared for final oocyte maturation in high responders undergoing GnRH-ant cycles. Results: Five retrospective studies were included for this review. Three of the studies showed that the use of dual trigger versus GnRH-a trigger resulted in no statistically significant difference in rates of OHSS while achieving a statistically significant difference in favor of the dual trigger group in ongoing pregnancy rates, early pregnancy loss, and fertilization rates. Conclusion: Currently, there is insufficient evidence to support improved clinical pregnancy rate, fertilization rate, live birth rate, and early pregnancy loss rate by the use of dual trigger versus GnRH-a trigger. Larger double-blind clinical studies are required to properly evaluate the efficacy of this protocol for use in high responders.